Self injury pada dewasa awal: Bagaimana peranan self awareness? - Shalsabilla, Rachmadintha Chantika Putri; Pratikto, Herlan; Aristawati , Akta Ririn (INNER: Journal of Psychological Research, 2023)
Everyone has their own self-awareness not to hurt themselves. If the person is able to maintain self-awareness, then there will be no tendency to hurt himself. The purpose of this study was to determine the relationship between self-awareness and the tendency of self-injury in early adulthood. The subjects in this study were early adults with an age range ranging from 20-25 years, students of the Faculty of Psychology in the 2019-2022 class. This study used correlational quantitative methods, with data analysis using Product Moment with the help of SPSS 23. The results obtained were -825 with sig. 0.000, which means that there is a significant negative relationship between the self-awareness variable and the tendency for self-injury in early adulthood. The higher the level of self-awareness you have, the lower the tendency for self-injury. Conversely, the lower the level of self-awareness, the higher the tendency for self-injury. Keywords: Early Adults, Self Injury, Self Awareness